Bibliometric and visual analysis in the field of tea in cancer from 2013 to 2023 - Lian, Yuanchu; Li, Xiating; Lan, Ying; Li, Zonghuai; Lin, Xiaoxin; Huang, Jing’an; Zhang, Bo; Feng, Zhongwen (Frontiers in Oncology, 2024)
Objective: Tea has been utilized in cancer research and is progressively gaining wider recognition, with its roles in cancer prevention and treatment being increasingly affirmed. The objective of this study is to investigate the current state and research hotspots in the field of tea's involvement in cancer research from 2013 to 2023, aiming to offer reference and direction for future studies. Methods: We analyzed 4,789 articles published between 2013 and 2022 from the Web of Science database using VOSviewer, R software, and CiteSpace software. Result: Tea-related cancer research showed an overall upward trend, with China leading in publications, followed by the United States, India, Japan, and Italy. China also had significant international collaborations, notably with Harvard University and the Egyptian Knowledge Bank. The 'Journal of Agricultural and Food Chemistry' was the most cited journal. Key topics included 'green tea,' 'cancer,' 'in vitro,' 'oxidative stress,' and 'apoptosis.' Research focused on tea's pharmacological effects, anticancer properties, mechanisms of natural compounds (e.g., polyphenols and EGCG), antioxidant and antimicrobial properties, and molecular mechanisms in cancer treatment. Conclusion: Tea's potential as an anti-cancer medication is gaining global recognition. Our study provides a comprehensive analysis of tea-related cancer research from 2013 to 2023, guiding future investigations in this field.